Doctor Strange [videorecording (DVD)] - Derrickson, Scott; Cumberbatch, Benedict, 1976-; Ejiofor, Chiwetel, 1977-; McAdams, Rachel, 1978-; Lee, Stan, 1922-2018 (Marvel Studios, 2017)
A former neurosurgeon embarks on a journey of healing only to be drawn into the world of the mystic arts.